Peran Pengeluaran Pemerintah, Infrastruktur, dan Tenaga Kerja dalam Meningkatkan Pembangunan Manusia dan Pertumbuhan Ekonomi di Bidaang Pendidikan - Vika Amalia Deantari; Deky Aji Suseno (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study analyzes the effect of government spending in the education sector, educational infrastructure, and teaching staff on the average length of schooling (ALS) and its effect on gross domestic product (GDP) in 34 provinces in Indonesia. The method used is Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results of the study show that education spending has a positive and significant effect on GDP, while educational infrastructure has a negative and significant effect. Teaching staff have a positive impact on average length of schooling, but do not have a direct impact on GDP. Average length of schooling has a positive impact on GDP and functions as a mediating variable in education variables and economic growth. These results indicate that average length of schooling has a strong mediating effect on economic growth by improving the quality of human resources.